Time Lag Application on Correlation Analysis among the national and international agencies for the rainfall data of Lampung Province, Indonesia - Lintang Kurnia Aridini; Ahmad Zakaria; Dyah I Kusumastuti; Ahmad Herison; Endro P Wahyono (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
The rainfall data in Lampung tends to be small and cannot represent a large location, so other sources of rainfall data are needed that can be used. One of them is TRMM on that basis it is deemed necessary to see the correlation of the TRMM and BMKG data. The purpose of this research is to analyze how big the correlation between TRMM data and BMKG data with Time Lag. And its Predictability, as well as improved correlation with Time Lag. The method used in this study is the Pearson correlation. The result of this research is that the biggest correlation is on H0 and H+1 for the highest daily cumulative 0.3376 - 0.4808, for cumulative 2 days at 0.417- 0.555, for cumulative 7 days 0.569 - 0.706, for cumulative 15 days at 0.612 - 0.785 and cumulative 30 daily 0.710 -0.811 the conclusion of this study is that TRMM and BMKG have a better correlation on H + 1 and (H0), the results of linear regression analysis with Time Lag concluded that the predictive ability of the data is better on Time Lag and the difference in correlation between H + 1 and H0 obtained an increase in the correlation value. declared to have increased 0.01 - 0.2).